SURGICAL MANAGEMENT OF DYSTOCIA IN A RAJAPALAYAM DOG DUE TO PRIMARY UTERINE INERTIA - M MURALI, REVATHY; M HARSHAN, HIRON; V K, VIDYA; PRATHAP, GAYATHRI; BABU, ANILA; BIRADAR, VINAYAK (The Indian Journal of Animal Reproduction, 2022)
A three year old primiparous female Rajapalayambitchcrossed 63 days back was presented to the Teaching Veterinary Clinical Complex (TVCC), Mannuthy, with a complaint of difficulty in whelping. Per vaginal examination revealed a foetus in the birth canal and bitchdid not exhibit any signs of uterine contractions and straining. Sonographic examination revealed viable foetuses with low heart beats. The foetus presented was expelled, following medical managementwithout any assistance and no further progress was observed. Remaining seven live pups present in the distended and extremely thin uteruswere recovered by conducting emergency caesarean section. The condition was clinically diagnosed as partial primary uterine inertia due to over distension of the gravid uterus.